“Psychoeducation” A Comprehensive Approach to Improve the Quality of Life of Patients with Coronary Heart Disease: A Scoping Review - Widiasih, Restuning; Khoirunnisa, Khoirunnisa; Aini, Farah Huwaida Qurrota; Megatami, Noviani; Nurfadillah, Nisa Nizhan; Fathurrizki, Ahmad Ihsan; Araujo, Glorianita A. R. (Universitas Padjadjaran, 2026)
Coronary heart disease is one of the diseases with acute and critical manifestations that has a high mortality rate worldwide. Psychoeducation is a comprehensive intervention that can be provided to acute patients, given its speed and its effects on all aspects of health. Comprehensive studies on the application of psychoeducation in acute-phase coronary heart disease patients are limited, so this literature review aims to identify the effectiveness of psychoeducation in managing this disease. This review uses a scoping review approach, applying six main stages: problem identification, identification of literature sources, literature selection, mapping and collecting literature, compiling and reporting results, and consulting with competent parties. The literature selection used the PRISMA approach, with article searches across three databases: Academic Search Complete, PubMed, and SAGE Journals. The studies reviewed used English-language research designs and focused on adult patients with acute or chronic coronary heart disease who received psychoeducation therapy, using RCT/cross-sectional/quasi-experimental/cohort study designs. The search results yielded five articles on the management of psychoeducation interventions in surgical and non-surgical conditions, focusing on coping strategies, physical capacity improvement, and disease understanding. Psychoeducation has been proven to improve patients' biopsychosocial quality of life (reducing stress levels, anxiety levels, depression, physical health, and social functioning). Psychoeducation can increase patients' knowledge by explaining coping strategies for adapting to life crises and other potential threats or developments. Further research is needed to refine the application of psychoeducational interventions on the quality of life of coronary heart disease patients